Seasonal nitrogen fluxes of the Lena River Delta - Tina Sanders; Claudia Fiencke; Matthias Fuchs; Charlotte Haugk; Bennet Juhls; Gesine Mollenhauer; Olga Ogneva; Paul Overduin; Juri Palmtag; Vasily Povazhniy; Jens Strauss; Robyn Tuerena; et al. (Ambio, 2022)
The Arctic is nutrient limited, particularly by nitrogen, and is impacted by anthropogenic global warming which occurs approximately twice as fast compared to the global average. Arctic warming intensifies thawing of permafrost-affected soils releasing their large organic nitrogen reservoir. This organic nitrogen reaches hydrological systems, is remineralized to reactive inorganic nitrogen, and is transported to the Arctic Ocean via large rivers. We estimate the load of nitrogen supplied from terrestrial sources into the Arctic Ocean by sampling in the Lena River and its Delta. We took water samples along one of the major deltaic channels in winter and summer in 2019 and sampling station in the central delta over a one-year cycle. Additionally, we investigate the potential release of reactive nitrogen, including nitrous oxide from soils in the Delta. We found that the Lena transported nitrogen as dissolved organic nitrogen to the coastal Arctic Ocean and that eroded soils are sources of reactive inorganic nitrogen such as ammonium and nitrate. The Lena and the Deltaic region apparently are considerable sources of nitrogen to nearshore coastal zone. The potential higher availability of inorganic nitrogen might be a source to enhance nitrous oxide emissions from terrestrial and aquatic sources to the atmosphere.

Nutrient pathways and their susceptibility to past and future change in the Eurasian Arctic Ocean - Robyn E. Tuerena; Claire Mahaffey; Sian F. Henley; Camille de la Vega; Louisa Norman; Tim Brand; Tina Sanders; Margot Debyser; Kirstin Dähnke; Judith Braun; Christian März (Ambio, 2022)
Climate change is altering nutrient cycling within the Arctic Ocean, having knock-on effects to Arctic ecosystems. Primary production in the Arctic is principally nitrogen-limited, particularly in the western Pacific-dominated regions where denitrification exacerbates nitrogen loss. The nutrient status of the eastern Eurasian Arctic remains under debate. In the Barents Sea, primary production has increased by 88% since 1998. To support this rapid increase in productivity, either the standing stock of nutrients has been depleted, or the external nutrient supply has increased. Atlantic water inflow, enhanced mixing, benthic nitrogen cycling, and land–ocean interaction have the potential to alter the nutrient supply through addition, dilution or removal. Here we use new datasets from the Changing Arctic Ocean program alongside historical datasets to assess how nitrate and phosphate concentrations may be changing in response to these processes. We highlight how nutrient dynamics may continue to change, why this is important for regional and international policy-making and suggest relevant research priorities for the future.

Temporal and spatial trends in marine carbon isotopes in the Arctic Ocean and implications for food web studies - Camille de la Vega; Rachel M. Jeffreys; Robyn Tuerena; Raja Ganeshram; Claire Mahaffey (Global Change Biology, 2019)
The Arctic is undergoing unprecedented environmental change. Rapid warming, decline in sea ice extent, increase in riverine input, ocean acidification and changes in primary productivity are creating a crucible for multiple concurrent environmental stressors, with unknown consequences for the entire arctic ecosystem. Here, we synthesized 30 years of data on the stable carbon isotope (δ 13 C) signatures in dissolved inorganic carbon (δ 13 C‐DIC; 1977–2014), marine and riverine particulate organic carbon (δ 13 C‐POC; 1986–2013) and tissues of marine mammals in the Arctic. δ 13 C values in consumers can change as a result of environmentally driven variation in the δ 13 C values at the base of the food web or alteration in the trophic structure, thus providing a method to assess the sensitivity of food webs to environmental change. Our synthesis reveals a spatially heterogeneous and temporally evolving δ 13 C baseline, with spatial gradients in the δ 13 C‐POC values between arctic shelves and arctic basins likely driven by differences in productivity and riverine and coastal influence. We report a decline in δ 13 C‐DIC values (−0.011‰ per year) in the Arctic, reflecting increasing anthropogenic carbon dioxide (CO 2 ) in the Arctic Ocean (i.e. Suess effect), which is larger than predicted. The larger decline in δ 13 C‐POC values and δ 13 C in arctic marine mammals reflects the anthropogenic CO 2 signal as well as the influence of a changing arctic environment. Combining the influence of changing sea ice conditions and isotopic fractionation by phytoplankton, we explain the decadal decline in δ 13 C‐POC values in the Arctic Ocean and partially explain the δ 13 C values in marine mammals with consideration of time‐varying integration of δ 13 C values. The response of the arctic ecosystem to ongoing environmental change is stronger than we would predict theoretically, which has tremendous implications for the study of food webs in the rapidly changing Arctic Ocean.